(untitled) (Proceedings of the International Conference on Education, 2021)
The COVID-19 pandemic has nurtured meaningful transformations in educational contexts; even highly traditional contexts were open about transforming approaches and methodologies. Medical professionals’ education relies heavily on presence-based interaction with patients, for example, to develop community activities such as patient education, which needed to continue despite the school lockdown. As part of an intervention, medical students designed a patient education and disease awareness campaign through social media. The objective of this study was to assess the transformation of patient education and disease awareness strategies to the new remote format. The methodology considered a quantitative approach with a descriptive, and cross-sectional design. The sample consisted of 34 medical students enrolled in an endocrine diseases course. Each team designed the material for the campaign based on the literature research they performed. Three tutors evaluated each team using a 5-point Likert scale addressing: disease, posts, survey, and overall assessment. Analysis of results included mean, standard deviation, and linear regression. With a correlation coefficient of 0.745 and a standard error of 0.21, the study found a high correlation between variables for each team. The results show that the transformation of this educational experience was key to offer an engaging educational learning experience for medical students. The campaigns held on social media platforms received a favorable response, as the engagement through comments and likes from their followers show, which helped on tunning the contents to relate closely to the specific audience.